A soft start-up method for DC micro-grid based on improved two-level VSC with DC fault ride-through capability - Wen, Weijie; Lyu, Rui; Li, Botong; Cao, Hong; Yu, Jiali; Li, Bin; Popov, Marjan (Frontiers in Energy Research, 2023)
Due to the progressive penetration and usage of renewable source, direct current (DC) micro-grid is getting broad attention. In general, for the black start-up of DC micro-grid, three-phase charging resistors are used to limit the starting current inside two-level voltage source converter (VSC). However, this method might take several seconds, and it is hard to adjust the charging resistance dynamically according to the variable capacitance so that surge charging current could be avoided. To solve this problem, a soft start-up method for DC micro-grid based on an improved two-level VSC with DC fault ride-through capability is proposed in this paper. The topology and control sequence of the improved two-level VSC is briefly introduced. The soft start-up method for DC micro-grid based on the flexible control of the improved two-level VSC is presented. Then, theoretical analysis of the transient current of the converter is discussed. In the end, a simulation model in PSCAD/EMTDC is established for verification. Simulation results have shown, regardless of the equivalent capacitance of the DC micro-grid, the soft start-up method can always ensure the starting current within its limit; in addition, the improved VSC has DC fault ride-through capability.